Baseline emotional state influences on the response to animated short films: A randomized online experiment - Negrão, Juliana Gioia; Bazán, Paulo Rodrigo; de Azevedo Neto, Raymundo Machado; Lacerda, Shirley Silva; Ekman, Eve; Kozasa, Elisa Harumi (Frontiers in Psychology, 2022)
Considering the relevance of the emotional state, it is necessary to understand how daily stimuli can modulate the emotions. Animated short films are common stimuli, but it is unknown how they can modulate the emotional state. The study aimed to evaluate: how participants' emotional state changed after watching animated short films with positive or negative emotional valence in an online experiment; the relationship between participants' baseline score on an Emotional Intensity Scale and their potential change of the main emotion after watching the films; and the association between the initial main emotion valence and the potential change in this emotion with participants’ social-demographic information. A sample of 2,269 participants recruited during COVID-19 pandemic, were randomly assigned to either watch a negative or positive animated short film. The results showed that, after watching a film with negative valence, participants were in a more negative emotional state than at baseline and compared with those who watched the film with positive valence. Also, individuals who had a negative baseline emotion and maintained the same emotion after the film, had presented higher baseline emotional state scores (more negative emotion) than those who changed their emotion. In addition, the individuals who kept the baseline emotion had an association with age, marital status, level of education and psychiatric disorders, use of medication, and emotional awareness, while the individuals who changed the baseline emotion had an association with age, gender and following or not social distancing recommendations.